Uncertainty in critical illness and the unexpected: important mediators in the process of nurse-family communication - Anabela Pereira Mendes (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: The purpose of this study was to understand, based on the Mishel's Theory of Uncertainty in Illness and the Theory of Transitions of Meleis, in which way uncertainty in illness and the unexpected mediated the process of nurse-family communication and are translated into lived experience of the family. Method: Considering the intentionality of the research, it fits into a qualitative paradigm and a phenomenological approach, according to Van Manen. Participants were referred to as "snowball" and the data collection was performed by interview with open questions. Results: In the analysis of the data, three essential themes were identified: The antecedents of uncertainty: condition inherent to the subject; The process of assessing uncertainty: capacities and opportunities; The way to deal with uncertainty: coping strategies. Conclusion and implications for practice: Family member who lives the uncertainty has personal conditions that influence the process of appreciation and deal with uncertainty. The communication that establishes with the nurses, in particular in the search for information, will be mediated by the experience of uncertainty, in a constant unforeseen. The adaptation that is desired and demanded arises from coping strategies developed, with the nurses too, considering uncertainty a danger or an opportunity.